Vertical up-flow constructed wetlands exhibited efficient antibiotic removal but induced antibiotic resistance genes in effluent. (July 2018) - Song, Hai-Liang; Zhang, Shuai; Guo, Jianhua; Yang, Yu-Li; Zhang, Li-Min; Li, Hua; Yang, Xiao-Li; Liu, Xi
Abstract: The intensive use of antibiotics results in their continuous release into the environment and the subsequent widespread dissemination of antibiotic resistance genes (ARGs), thus posing potential risks for public health. Although vertical up-flow constructed wetlands (VUF-CWs) have been widely used to treat wastewater in remote or rural regions, few studies have assessed the potential risks of ARG dissemination when VUF-CWs are applied to treat wastewaters containing antibiotics. In this study, the removal performance of two typical antibiotics (sulfamethoxazole (SMX) and tetracycline (TC)) and the fate of ARGs were evaluated in three lab-scale VUF-CWs. The results indicated that high removal efficiencies (>98%) could be achieved for both SMX and TC. However, the exposure of antibiotics resulted in harboring abundant ARGs (mainly sul - and tet -related genes), even with increasing abundances with operation time. The abundances of ARGs had a positive correlation with the accumulation of SMX and TC in different layers of VUF-CWs, where the tet and sul genes have the highest abundance in the bottom layer due to the highest antibiotic exposure concentration. Positive correlations were observed between the abundance of tet gene and antibiotic concentration in effluent. Although the effluent had lower abundances of the ARGs than that in the wetland media, the occurrence of ARGs in effluent might still pose risk for public health. Further studies are required to explore effective control strategies to eliminate ARGs from VUF-CWs. Graphical abstract: Highlights: Sul and tet genes showed an increase in wetland substances. Effluent possessed lower abundances of ARGs than that in wetland media. Positive correlations between 16S rRNA and ARG copy numbers in effluent. ARGs may be spread via effluent due to antibiotics removal by VUF-CW. Elimination of total microbes in effluent might inhibite spread of ARGs.